Emergence of multidrug-resistant ST11 blaKPC-2 producing Klebsiella pneumoniae coharboring blaCTX-M and blaSHV in Pakistan - Aamir Jamal Gondal; Sidrah Saleem; Nakhshab Choudhry; Fridoon Jawad Ahmad; Hina Bukhari; Nighat Yasmin; Shah Jahan (Journal of Infection in Developing Countries)
Introduction: Carbapenemases are primarily responsible for the intensified spread of multidrug-resistant (MDR) K. pneumoniae by virtue of antibiotics overuse. Therefore, frequent investigation of high-risk clones especially from developing world is crucial to curtail global spread.